Discovering Italian Free Metal Reeds: A Fieldwork Enquiry - Pinelli, Raffaele (European Journal of Musicology, 2022)
This article presents some of the results achieved in the complex and still little-known production system of metal free reeds for mechanical bellows aerophones. It starts from the encounter with Lorenzo Antonelli, director of the Italian factory "Voci Armoniche", which is one of the oldest and most important in the world. The account of this encounter will be used to demonstrate how intensive fieldwork research in ethnomusicology (i.e. the practice of cyclical alternation of phases in situ and ex situ) can mutually enrich the knowledge of both observer and observed and, at the same time, stimulate changes in individuals, as well as in the objects covered by the survey. The methodological structure of the article is based on the account of my fieldwork experiences, used here as an anthropological approach, with the intent of clarifying some crucial aspects of research on oral transmission contexts within an aural culture. Finally, this article aims to contribute to the debate on the relation between basic and applied research in the context of ethnomusicological, organological studies and research on the anthropology of techniques.